PENGARUH BUDAYA ORGANISASI, INSENTIF, MOTIVASI KERJA TERHADAP PENGARUH KINERJA PEGAWAI SEKRETARIAT DAERAH KABUPATEN PANGKAJENE DAN KEPUALAUAN - Nur Amaliah Suyuti; Muhammad Idris; Syamsul Alam (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat ITB Nobel Indonesia, 2020)
This study aims to determine and analyze: The Effect of Organizational Culture, Incentives and Work Motivation on the Performance of Employees of the Regional Secretariat of Pangkajene and Kepulauan Regency, as well as the most dominant variable impact employee performance at the Regional Secretariat of Pangkep Regency. This reserch approach uses survey research.The study population was all 103 Pangkep Regency Secretariat employees.The sample selection in this study was carried out using the saturated sampling method (census), namely by determining all populations as a total sample of 103 employees.Data analysis uses multiple regression analysis uses multiple regression analysis (multiple regression analysis). The results of this study indicate that the first hypothesis both partially and simultaneously organizational culture variables, work incentives and motivation have a positive and significant effect on the performance of pangkep District Sekretariat employees,the second of the three independent variables the results of the study indicate that the organizational culture variable is the most dominant influence on the performance of the employees of the Regional Secretariat of the Pangkajene Regency and the Islands because they have beta or standardizet coefficient numbers greater than other variables. Abstrak Pendekatan penelitian ini menggunakan penelitian survey. Populasi penelitian adalah semua pegawai Sekretariat Daerah Kabupaten Pangkep yang berjumlah 103 orang. Pemilihan sampel dalam penelitian ini dilakukan dengan menggunakan metode sampling jenuh (sensus) yakni dengan menentukan semua populasi sebagai sampel total sebanyak 103 orang pegawai. Analisis data menggunakan analisis regresi berganda (multiple regression analysis). Hasil penelitian ini menunjukkan bahwa hipotesis pertama baik secara parsial dan simultan variabel budaya organisasi, insentif dan motivasi kerja berpengaruh positif dan signifikan terhadap kinerja pegawai Sekretariat Daerah Kabupaten Pangkep, kedua dari tiga variabel bebas tersebut hasil penelitian menunjukkan bahwa variabel budaya organisasi yang paling dominan pengaruhnya terhadap kinerja pegawai Sekretariat Daerah Kabupaten Pangkajene dan Kepulauan karena mempunyai angka beta atau standardizet coefficient lebih besar dari variabel lainnya.